Análise das recidivas de malária causada por Plasmodium vivax no município de Porto Velho, Rondônia, 2009 - Simões, Luciano Rodrigues (2012)
In 2011, 293,794 malaria cases were registered in Brazil, with more than 85% caused by Plasmodium vivax. The state of Rondonia had the third highest incidence of the disease. The term recurrence of a disease refers to the recurrence of symptoms after a period of time longer or shorter since the recovery or cure. Recurrence of malaria can be caused by treatment failure, reactivation of dormant form of the parasite or reinfection by a mosquito bite, classified as recrudescence, relapse and reinfection, respectively. The National Malaria Control Programme defines as P. vivax recrudescence the recurrence of parasitemia between 7 to 28 days after the beginning of treatment. As P. vivax relapse the recurrence ocurring between 29 and 60 days and reinfection as the reappearance of the parasitemia after 60 days of the treatment. This study described the recurrence risk for malaria caused by P. vivax in the city of Porto Velho (RO) in 2009. An open retrospective cohort study was performed, using the malaria information registered in the Epidemiological Information System for the Surveillance of Malaria (SIVEP-Malaria). In 2009, there were 23.365 P. vivax malaria cases in Porto Velho, 23% of them having P. vivax malaria recurrence during the year of study. The largest proportion (67%) of patients who recurred had a single episode of recurrence, although several patients have experienced multiple recurrences in the year. The incidence density of recurrence observed in the study period was 45.1/100 person-years, mostly occurring between the 4th and 13th week after treatment initiation. Being male, having less time of symptoms and having a higher level of parasitemia at diagnosis of P. vivax malaria increase the risk of recurrence during the follow-up. The found associations were 11% and 15% of risk increasing for males and for higher levels of parasitemia at diagnosis, respectively, and 10% of risk reduction for longer time of onset of symptoms. However, these low values of the risk measures represent a very low clinical relevance of these associations, undermining its causal relationship to predict the incidence of P. vivax recurrence or to justify decision making in public health.